(untitled) (MCIT: Proceedings of International scientific and practical conference, 2025)
У статті розглядаються адаптивні нейромережеві моделі для оцінювання та регулювання когнітивного навантаження у навчальних комп’ютерних іграх. Запропоновано підхід із застосуванням online learning на основі рекурентних нейромереж (LSTM/GRU) та механізму Elastic Weight Consolidation (EWC) для стабільності дрейфу моделі. Пропонована система використовує мультимодальні дані такі як ігрові метрики та поведінкові показники для динамічного регулювання складності навчального процесу. Представлено концепцію експериментальної реалізації із порівнянням online та offline методів навчання. Оцінюється потенціал підходу в підвищенні ефективності навчання та залученості користувачів. The article discusses adaptive neural network models for assessing and regulating cognitive load in educational computer games. An approach is proposed that applies online learning based on recurrent neural networks (LSTM/GRU) and the Elastic Weight Consolidation (EWC) mechanism to ensure model drift stability. The proposed system utilizes multimodal data such as gameplay metrics and behavioral indicators to dynamically adjust the difficulty of the learning process. The concept of an experimental implementation is presented, including a comparison between online and offline training methods. The potential of the proposed approach in enhancing learning efficiency and user engagement is evaluated.